(untitled) (CIPEEX, 2023)
The present work presents the ’State of the Art’ scheduled for the preparation of a Master’s Thesis being developed in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda highlights the importance of studies focused on the effectiveness of Brazilian judicial provision aimed at the environmental protection of Permanent Preservation Areas (APP) in streams, especially the Água Fria Stream located in the municipality of Anápolis/Goiás. In 2012, two legal actions were proposed within the Judiciary of the Anápolis District: a Public Civil Action with a focus on obligations to do and not do, as well as environmental damage repair, and another, a Criminal Action to investigate any environmental crimes committed. The environmental damages were evident. The criminal action was dismissed and archived in the year 2022 without a judgment on the merits, due to the subsequent expiration of the state punitive prescription. The Public Civil Action also did not achieve the initially expected result, although it is still ongoing. To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, allowing the development of research of a descriptive and explanatory nature.